Legal Protection for Business Actors Against Losses Arising from Product Returns in Electronic Transactions on TikTok Shop - Siti Farul Balqis; Azhari Azhari; Sanusi Sanusi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The return policy implemented by TikTok Shop reflects an imbalance in legal protection between consumers and business actors. Although Article 6 letter a of Law Number 8 of 1999 concerning Consumer Protection guarantees business actors’ rights to receive payment according to agreed terms, and Article 5 letter b requires consumers to act in good faith, return mechanisms are often misused through unjustified requests, mismatched product returns, and manipulative practices causing financial losses. This study aims to analyze the regulatory framework of TikTok Shop return policies, legal protection for losses suffered by business actors, and available dispute resolution mechanisms. This research applies an empirical juridical method with a qualitative approach through literature review, observation, and interviews. The findings indicate that TikTok Shop’s return policy is a standard contract binding business actors through a clickwrap agreement. However, the Speedy Refund mechanism has not ensured balanced protection due to automatic refunds without adequate verification. Legal protection is provided through preventive regulations and repressive mechanisms, including appeals, dispute settlement bodies, Online Dispute Resolution, and courts. Strengthening digital platform regulations and verification systems is required to achieve fair legal protection.